Approximation to the social cohesion and its relation with the avoidable mortality in Chiapas's childhood, Mexico, 2015 - Lizárraga Bustamante, Gilberto Martín (2018)
Objective: To relate the information of the childhood rate of mortality due to diarrhea and gastroenteritis of supposed infectious origin or TMN A(090-099) with the social cohesion degree (GCS). Methods: It is a transverse and ecological study for the year 2015. The municipal TMN A(090-099) was calculated with the National System in Health Information (SINAIS) deaths records. The approximation towards the social cohesion was done with the National Council for the Evaluation of the Social Development Policy (CONEVAL) through the municipal Social Cohesion Degree (GCS). A bivariate correlation was calculated with Spearman test. The correlation between the TMN A(090-099) and the GCS was obtained. Also a model was calculated: TMN A(090-099) as the dependent variable confronted with the GCS, Gini's index, social blacklog index and the lack of medical services. Results: A negative relation between the GCS and the TMN TO (090-099) was found, with significant but weakly correlation (-0.320 **); the hypothesis is accepted with reservations. The model presents moderate and positive correlation (R=0.554), the square R suggests that the model explains almost 27 % of the cases, and the Durbin-Watson value suggests that the model covers almost 90 % of the studied cases. Discussion: The social cohesion in Chiapas is very subdued. There are municipalities with very high TMN A(090-099) and lower social cohesion degree besides high social backlog degree; this scene prevails, but is necessary to restate the usefulness of the qualitative boarding as recommendation found in social cohesion literature.